2005
DOI: 10.1007/s00408-005-2549-0
|View full text |Cite
|
Sign up to set email alerts
|

Basis of Rise in Intracellular Sodium in Airway Hyperresponsiveness and Asthma

Abstract: The aim of this study was to investigate the basis of disturbances in sodium transport in asthma and in airway hyperresponsiveness without symptoms of asthma (asymptomatic AHR). We measured the intracellular sodium (Na(i)); activity of Na(+)/K(+)-ATPase in unstimulated cells (resting activity) and in cell homogenate under optimal conditions (maximal activity); and sodium influx, in mixed leukocytes of 15 normal subjects, 12 subjects with asymptomatic AHR, and 26 asthmatics with or without active symptoms. Rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
3
7
0
1
Order By: Relevance
“…This finding was supported by a barrage of studies that suggested the existence of a serum-borne inhibitor of the Na ϩ /K ϩ pump in subjects with allergic rhinitis and/or allergic asthma (3,13,23,54,55,64). This unknown factor increased intracellular [Na ϩ ], decreased uptake of Rb ϩ , and decreased overall activity of the Na ϩ /K ϩ pump in isolated human platelet, leukocytes, and peripheral blood mononuclear cells (3,13,23,54,55,62,64). Furthermore, the plasma from allergic individuals could inhibit Rb ϩ uptake in leukocytes from control (i.e., nonallergic) individuals.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…This finding was supported by a barrage of studies that suggested the existence of a serum-borne inhibitor of the Na ϩ /K ϩ pump in subjects with allergic rhinitis and/or allergic asthma (3,13,23,54,55,64). This unknown factor increased intracellular [Na ϩ ], decreased uptake of Rb ϩ , and decreased overall activity of the Na ϩ /K ϩ pump in isolated human platelet, leukocytes, and peripheral blood mononuclear cells (3,13,23,54,55,62,64). Furthermore, the plasma from allergic individuals could inhibit Rb ϩ uptake in leukocytes from control (i.e., nonallergic) individuals.…”
supporting
confidence: 68%
“…The magnitude of this effect was well associated with the degree of airway dysfunction in the donor subjects (62). These data were confirmed by two more recent studies that reported an association between Na ϩ /K ϩ pump inhibition and resulting intracellular Na ϩ accumulation and increased severity of airway dysfunction (3,13).…”
supporting
confidence: 56%
“…This pump is very sensitive to inhibition by cardioactive steroids, particularly the group of digitalis and ouabain used to treat congestive heart failure and arrhythmias (20). Abundant sources report the presence of a 'serum factor' (most probably ouabain) that inhibits the function of NKA (2126). Endogenous ouabain has been characterized as a steroidal glycoside found in blood plasma and is synthesized by the adrenal glands, hypothalamus and pituitary (2733).…”
Section: Na+/k+atpasementioning
confidence: 99%
“…Multiple studies of patients with atopic asthma and/or allergic rhinitis report the presence of plasmatic, endogenous ouabain, indicating a probable intracellular Na + accumulation (2126). In fact, the study by Tribe et al (25) shows an increased intracellular Na + concentration in mononuclear cells from healthy individuals incubated with plasma of asthmatic blood donors.…”
Section: Evidence Of Na+ Participation In Asthmamentioning
confidence: 99%
“…Изучению активности транспортных систем Na + и K + у больных с бронхолегочной патологией и, в част ности, с бронхиальной астмой (БА) был посвящен ряд исследований как в нашей стране [1,2], так и за рубежом [3,4]. На рубеже XIX-XX вв.…”
Section: оригинальные исследованияunclassified